Clinical outcome of fistulectomy with partial sphincter preservation in complex fistula-in-ano in a tertiary hospital of Bangladesh - Ahmed, Jalal; Ullah, M. Meher; Aman, Asif; Mondal, Satya Ranjan; Qurashi, Sabrina Akhter; Mustafa, Golam; Habib, Ahsan; Faruk, Imtiaz (International Surgery Journal, 2025)
Background: Complex fistula-in-ano poses a significant surgical challenge due to its high recurrence risk and potential for sphincter damage leading to incontinence. Sphincter-preserving fistulectomy aims to balance effective tract removal with continence preservation. This study evaluated clinical outcomes of fistulectomy with partial sphincter preservation in patients with complex fistula-in-ano. Methods: This prospective observational study was conducted in the Department of Surgery at Dhaka Medical College Hospital, Dhaka, Bangladesh, from January 2023 to June 2024. A total of 77 patients with complex fistula-in-ano underwent fistulectomy with partial sphincter preservation. Preoperative evaluation included clinical and radiological assessment. Surgery involved careful dissection and excision of the fistula tract while preserving part of the external anal sphincter. Patients were followed up for six months and outcomes assessed included wound healing time, postoperative complications, continence status, recurrence and satisfaction. Data were analyzed using SPSS version 25. Results: The mean age of patients was 38.6±10.4 years, with 79.2% being male. The most common fistula type was trans-sphincteric (55.8%). Mean operative time was 45±12 minutes and hospital stay averaged 2.3±1.1 days. Complete wound healing occurred in 92.2% of patients within a mean of 5.8±1.2 weeks. Recurrence was observed in 5.2%, while 2.6% experienced minor gas incontinence; no major incontinence was reported. Postoperative complications included wound infection (7.8%). Patient satisfaction was high in 85.7% of cases. Conclusions: Fistulectomy with partial sphincter preservation is an effective surgical approach for complex fistula-in-ano, offering high healing rates, low recurrence and excellent continence preservation.